The Relationship Between Accessibility Factors and Post-Inpatient Control Visits Among Non-JKN Participants at Hospital X - Candaika, Putri; Ningsih, Desy Kartika; Hartono, Risky Kusuma (UI Scholars Hub, 2026)
The rate of post-inpatient control visits remains relatively low due to various factors, including accessibility. At Hospital X, 220 of non-Jaminan Kesehatan Nasional (JKN) participants scheduled for post-inpatient control visits between January and March 2025, 71.82% attended, and 28.18% did not. Patients who did not attend control visits were twice as likely to be readmitted. This study aimed to determine the relationship between accessibility and post-inpatient control visits for non-JKN participants at Hospital X. This quantitative study employed an analytical cross-sectional design, with a population of 220 patients and a sample of 142 patients selected using probability sampling. Bivariate and multivariate analyses were performed using the chi-square test and binary logistic regression analysis. The results showed a significant relationship between distance to the hospital (p = 0.000), availability of transportation (p = 0.000), and the condition of service infrastructure (p = 0.000) with post-inpatient control visits among non-JKN participants at Hospital X. The results also showed that the factor with the highest probability of increasing post-inpatient control visits was walking as a mode of transportation, which increased the likelihood by 11.759 times. In conclusion, distance accessibility, transportation availability, and the condition of service infrastructure were significantly associated with post-inpatient control visits among non-JKN participants at Hospital X. The hospital should consider providing telemedicine services for patients who live at a considerable distance. In addition, the hospital could provide free pick-up and drop-off services within a certain radius.